Promoting Dialogic Action through the Expansion of English Language Learners' Communicative Repertoires - John Steven Gómez-Giraldo (Asociación Colombiana de Profesores de Ingles, 2022)
This action research study sought to foster dialogic action through the expansion of English language learners' communicative repertoires in a 6th-grade class at a public school in a Colombian town. During the first action research cycle, the restricted concept of communication of the grammar-based syllabus and the competitive and violent interactions between the learners were identified as key issues to address. From a critical perspective of pedagogy and literacy, this study understands that communication in language education should transcend the use of a standard target language, and include multiple linguistic codes and multimodal representative forms. Considering these principles and the issues identified, we designed an action plan for the second action research cycle. This plan consisted of activities that sought to expand English language learners' communicative repertoires and promote reflections on violence and conflict resolution through the analysis and creation of different visual representations. Data were collected through journal entries, semi-structured interviews, and students' artifacts. Findings show how the learners have a diverse and differentiated access to communicative repertoires and how they manipulated available representations to transform meanings. As a conclusion, not enough evidence of the emergence of dialogic action was found since competitiveness and violent interactions in the classroom did not significantly change during the intervention. Nonetheless, embracing the learners' communicative practices created spaces for reflection on complex social and moral topics in the classroom, even if their English linguistic resources were still limited.